Magnetic properties and magnetic phase transition in square-octagon lattice: Monte Carlo study. (3rd July 2021) - Jabar, A.; Masrour, R.; Hamedoun, M.; Benyoussef, A.; Hourmatallah, A.; Benzakour, N.; Rezzouk, A.; Bouslykhane, K.; Kharbach, J.
ABSTRACT: The magnetic properties and magnetic phase transition in square-octagon lattice with mixed spins 3/2 and 5/2 were investigated by Monte Carlo simulations. The ground state phase diagrams of square-octagon structure were obtained under the effect of crystal field and exchange interactions. The thermal partial, total magnetizations and magnetic susceptibilities of square-octagon lattice are obtained for a fixed magnetic parameter. The reduced Néel temperature is noticed. The variation of total magnetizations with the crystal field of square-octagon structure is shown. The magnetic hysteresis cycle of square-octagon structure, with mixed spins S   = 3/2 and σ   = 5/2 for several exchange interactions, temperatures and crystal fields, is found.